Modeling and controller design of a micro gas turbine for power generation. (May 2022) - Lin, Ping; Du, Xian; Shi, Yan; Sun, Xi-Ming
Abstract: This paper investigates the modeling and controller design of a micro gas turbine in power generation scenario. From the perspective of the controller design, it is well recognized that an accurate model in possession of the complex dynamic characteristics of a micro gas turbine is paramount. Thus, a nominal nonlinear model originated from integrating the start-up model and the component characteristic map model together is established to depict the main operating modes of the full operation envelope, containing the start-up mode, loading mode and unloading mode. The start-up model is got by the combination of polynomial fitting method with identification method. The component characteristic map model is achieved by combining inter-component volume method with experiment data. The proposed nominal nonlinear model is realized in MATLAB/Simulink environment. Furthermore, nonlinear and linear active disturbance rejection controllers and a PID controller are designed respectively. Such controllers not only realize the speed tracking control from the idle speed to the nominal speed, but also achieve the load tracking control at the nominal speed by numerical simulations and hardware-in-the-loop tests. In addition, the nonlinear active disturbance rejection controller has the best control performance, which is validated through the simulation results and hardware-in-the-loop tests.